The effect of cellular and physiological indicators on gender determination - Haje, Milat Ismail (Cellular and Molecular Biology, 2021)
Gender determination, in addition to having special value to parents, has particular importance in sex-linked diseases. This study aimed to investigate the cellular indicators (i.e. BMP-6 protein and PPAR? protein expression levels in granulosa cells) and the physiological indicators on gender determination. For this purpose, on 68 infertile patients referred to the clinic, ovarian stimulation was performed by different protocols and then ruptured by different HCG. Follow-up of patients was performed after they became pregnant after five months. U/S was done for knowing the gender of the baby then after labor rechecked another time. Also, granulosa-luteal cells (GLCs) were isolated from the follicular fluid of 68 women participating in the study. BMP-6 protein and PPAR? protein were measured using Western blotting. Results showed that the total number of delivered babies was 68, 41 males (60.3%) and 27 females (39.7%). About physiological indicators results, there was no significant association between the age of the mother and sex of the baby (P=0.934). No significant association was detected between the month during which the conception occurred and the sex of the baby (P=0.734). The same result was obtained for the follicle side (P=0.236), and follicle size (P=0.659), there was no significant association between the sex of the baby with the following factors: protocol of treatment (P=0.417), IVF after HCG (P=0.237), HCG type (P=0.572), parity (P=0.282), and type of infertility (P=0.376). The cellular indicators results showed that the BMP-6 protein level in granulosa cells of mothers with daughters was almost twice as high as mothers with sons (P=0.043). But there was no significant difference between mothers with daughters and mothers with sons in PPAR? protein level (P=0.12). It can be concluded that except for BMP-6 protein level, none of the cellular and physiological indicators affects gender determination. Therefore, this cell indicator can probably be evaluated as an effective indicator in determining gender.